P-P46 The use of FDG-PET/CT in the pre-operative staging of pancreatic ductal adenocarcinoma. (16th December 2021) - Jordan, Rebecca; Muir, Duncan; van Laarhoven, Stijn; Falk, Stephen; Strickland, Andrew; Skipworth, James
Abstract: Background: The NICE Quality Standard for Pancreatic Cancer (December 2018) recommends that ' adults with localised pancreatic cancer on CT(should) have staging using fluorodeoxyglucose positron emission tomography/CT(FDG-PET/CT) before they have surgery, radiotherapy or systemic therapy '. Such FDG-PET/CT staging aims to provide additional information to conventional cross-sectional imaging, thus presenting the most accurate staging of disease. However, the sensitivity and specificity of FDG-PET/CT to deliver relevant additional clinical information must be balanced with potential delays to treatment, and additional cost associated with its use, in the management of a time-critical pathology. Methods: Consecutive pancreatic ductal adenocarcinoma(PDAC) patients deemed resectable on conventional imaging, and therefore referred for FDG-PET/CT assessment, were included for analysis. Data were derived from a single tertiary Hepatopancreaticobiliary(HPB) centre between May 2018 and June 2021. Data were collected and analysed from a combination of prospectively-collated electronic databases and paper patient records. Results: Of 89 patients analysed, 55(61.7%) patients were male. Primary pancreatic lesions were PET avid in 81 cases(91%). Median time from request to FDG-PET/CT performance was 11 days(Range 1-35). Additional clinical information from FDG-PET/CT was provided in 61(68.5%) patients. Further investigations to assess FDG-PET/CT findings were arranged in 23 patients(25.8%; including liver MRI and EUS), demonstrating that FDG-PET/CT findings were true-positive in 6(26.1%), false-positive in 15(65.2%) and equivocal in 2(8.7%). There was a median delay of 60.5 days(Range 26 to 256) from FDG-PET/CT to surgery in those undergoing additional investigation. In total, a new diagnosis of metastatic/non-resectable disease was made in 14(15.7%) patients, preventing progression to planned operative intervention. Conclusions: FDG-PET/CT provided additional information to conventional imaging that led to cancellation of planned operative resection in 14(15.7%) PDAC patients-8 directly and 6 following further investigation. However, there was a median delay of 11 days to FDG-PET/CT and 60.5 days from FDG-PET/CT to surgery in those undergoing additional investigation. Whilst FDG-PET/CT can lead to avoidance of unnecessary surgical intervention in PDAC patients with unsuspected metastatic/non-resectable disease, it can lead to delay, over-investigation, excess cost and anxiety in resectable patients. HPB units should audit their own findings to assess whether the use of FDG-PET/CT should be considered on a standard or selected basis.